THE EFFECTIVENESS OF MCTS LEARNING MODEL TO IMPROVE CRITICAL THINKING SKILLS AND DISPOSITION - Fenno - Farcis (Universitas Negeri Surabaya, 2019)
MCTS learning model (Making Critical Thinking Students) is a learning model that refers to self regulated learning and uses ICT as a learning media. The purposes of this study was to analyze the effectiveness of the MCTS model to improving the critical thinking skills and disposition of students. This research was carried out to physics education students of Palangka Raya University who was attended the research methodology lecture. The effectiveness of the MCTS learning model is based on (1) the results of critical thinking skills and disposition of students and (2) students respons to the model. The results of the study show that critical thinking skills of physics education students at Palangka Raya University have increased significantly, with Î± = 5%, N-gain average critical thinking skills are consistently at very high criteria. Critical thinking disposition of learning a significant increase in positive criteria. Physics education students at Palangka Raya University averaged 95.33% giving a positive respons to MCTS learning model and its devices. Conclusion based on the results of the study of the effectiveness of the MCTS learning model is effective applied in learning to improve the critical thinking skills and disposition of physics education students of Palangka Raya University as a candidate physics teachers.